2021
DOI: 10.37120/ijttl.2021.17.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Top 20 Evidence-based Humor Techniques for Online Teaching: Building on a Half-century of Research and Practice

Abstract: The COVID-19 pandemic upended higher education in March 2020 and has continued into 2022. Within days of the international lockdowns, an emergency conversion from face-to-face (F2F) to remote learning occurred. Educators scrambled to convert their in-class teaching into some version of online teaching. The transformations ignited a surge in e-learning platforms. Combining PowerPoint (PPT) or Keynote with those platforms enabled several forms of humor to be presented by any professor in online teaching. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(89 reference statements)
0
0
0
Order By: Relevance
“…These studies have found that for face-to-face courses, student responses drop significantly when they are asked to rate the course using an online tool (Gerbase, Germond, Cerutti, Vu, & ). This problem is believed to be magnified when the course itself is delivered online (Berk, 2012). The results obtained in this study provide support for this belief based on the finding that while the average student enrollment in a course is 3,169, the average number of reviews is only around 276.…”
Section: Discussionsupporting
confidence: 63%
“…These studies have found that for face-to-face courses, student responses drop significantly when they are asked to rate the course using an online tool (Gerbase, Germond, Cerutti, Vu, & ). This problem is believed to be magnified when the course itself is delivered online (Berk, 2012). The results obtained in this study provide support for this belief based on the finding that while the average student enrollment in a course is 3,169, the average number of reviews is only around 276.…”
Section: Discussionsupporting
confidence: 63%
“…The current study examined the effect of increasing transparency on students' faith and participation in end-of-course SET, as transparency is recognised as an important measure to increase SET participation (Berk 2012;Hoel and Dahl 2019). Building on a study in which a text-based intervention showing course specific changes to students to increase SET transparency yielded little results (Nederhand et al 2023), we took an alternative approach by developing an animation showing the general SET process to students, untied to a specific course.…”
Section: Discussionmentioning
confidence: 99%
“…While they focused in their study on showing students how their detailed comments were applied, negative impact on response rate and quality appears to also stem from students being unaware of certain aspects of the general SET process. For example, it is recommended to make students aware of multiple aspects of the general SET process, such as why SET are collected, how and by whom their feedback is being used to improve aspects of education, and anonymity (Chen and Hoshower 2003;Berk 2012;Keeley et al 2013).…”
Section: Set Process Transparencymentioning
confidence: 99%
See 2 more Smart Citations